2015
DOI: 10.3168/jds.2015-9403
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic parameters for thermal denaturation of ovine milk lactoferrin determined by its loss of immunoreactivity

Abstract: Lactoferrin is a protein with important biological functions that can be obtained from milk and by-products derived from the dairy industry, such as whey. Although bovine lactoferrin has been extensively studied, ovine lactoferrin is not quite as well known. In the present study, the effect of several heat treatments in 3 different media, over a temperature range from 66 to 75°C, has been studied on lactoferrin isolated from sheep milk. Denaturation of lactoferrin was determined by measuring its immunoreactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…The degradation of Lf at elevated temperatures was also quantitatively evaluated using the RP-HPLC method. The degradation of Lf in aqueous solution at 50-80 • C best fitted the zero-order kinetic model (Table 6) This is not in line with literature data that report either first or 1.5 order kinetics [34][35][36]. However, the determination coefficients (R 2 ) obtained in our study for the zero-order model were higher compared to those found in other research articles.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The degradation of Lf at elevated temperatures was also quantitatively evaluated using the RP-HPLC method. The degradation of Lf in aqueous solution at 50-80 • C best fitted the zero-order kinetic model (Table 6) This is not in line with literature data that report either first or 1.5 order kinetics [34][35][36]. However, the determination coefficients (R 2 ) obtained in our study for the zero-order model were higher compared to those found in other research articles.…”
Section: Discussioncontrasting
confidence: 73%
“…The activation energy calculated from the Arrhenius plot was found to be 78.4 kJ/mol, which is lower than values found in the literature. However, a completely different analytical technique was used in these studies [ 34 , 35 , 36 ]. The differences could also be due to different iron saturation and glycosylation patterns of Lf and/or media used in stability studies [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally whey proteins are susceptible to heat treatment [ 5 , 6 ], particularly immunoactive proteins such as lactoferrin or lactadherin [ 7 ]. Heating of heat-labile proteins results in denaturation and aggregation processes [ 8 ] and thereby leads to a loss of biological functionality (e.g., lactoferrin [ 9 ]). Denatured and aggregated proteins can be extracted from the milk with a combination of pH reduction and ultracentrifugation [ 10 ], after which remaining levels of non-aggregated milk serum proteins can be determined [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A current study using a rheometer for heat-treating LF with an iron saturation of about 9-10% showed that treatment at temperatures of 72-95°C caused irreversible changes in the structural and physicochemical properties of LF (Goulding et al 2021). Although LF does not lose its immunoreactivity under pasteurisation (72°C, 15 s) conditions, inappropriate heat treatment (80°C, 10 min) caused a reduction of its regular secondary structure elements (Navarro et al 2015). Denaturation and aggregation of LF under heat treatment are thought to be influenced by many factors, such as iron saturation.…”
Section: Introductionmentioning
confidence: 76%